Navigating multiple identities race, gender, culture, nationality, and roles - Josselson, Ruthellen; Harway, Michele (Oxford : Oxford University Press, 2012)
In our increasingly complex, globalized world, people often carry conflicting psychosocial identities. This volume considers individuals who are navigating across racial minority or majority status, various cultural expectations and values gender identities, and roles.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Group identity; Identity (Psychology); Ethnicity; Gender identity; Nationalism; Social role